Genotype and NaCl salinity influence Pythium ultimum damping-off in safflower - Pahlevani, M.; Bagmohamadi, H.; Ghaderi, M.; Razavi, S. E. (Plant Breeding and Seed Science, 2013)
Increased seed germination and seedling growth in soils infected with damping-off pathogen, Pythium ultimum, especially under saline conditions, are important goals in safflower breeding programs. Seeds of four safflower varieties were cultured on germination media moistened with solutions of NaCl containing 105 zoospores of the pathogen per ml. NaCl concentrations were adjusted to produce salinities 0, -10, -14 and -18 bar. Analysis of variance indicated that the interactive effects of salinity, cultivar and pathogen significantly altered seed germination and seedling dry weight. In the absence of P. ultimum, increasing salinity significantly reduced seedling dry weight, but in pathogen-inoculated media, different values were observed. In the absence of salinity, the germination rate of inoculated seeds was 16.3% lower than that of non-inoculated seeds, whereas in a saline bed, the pathogen increased seed germination about 3.1 %. This finding clearly indicates that sodium chloride can reduce the pathogenesis of P. ultimum on safflower seedlings. The results showed that the presence of NaCl in the environment prevented rotting effects of the pathogen on seeds but intensified the mortality effect on seedlings. The simultaneous effects of salinity and pathogen reduced the usual adverse effects of either factor when applied separately. Thus, depending on amount of NaCl and/or Pythium infection present, different varieties are recommended to achieve an acceptable establishment and production.